Comparative genomics provides insight into maize adaptation in temperate regions. Issue 1 (December 2016) - Hufford, Matthew
Abstract A new study provides insights into the evolution of maize during its global spread into temperate regions from its origin in coastal Mexico. Please see related Research article:http://genomebiology.biomedcentral.com/articles/10.1186/s13059-016-1009-x